Identification Coliform Bacteria In Student Drinking Water In The Al-Mu'aawanah Boarding School, District Rajadesa, Ciamis District - Undang Ruhimat; Rivana Ariyadi; Rahayu Nirmatul; Fatna Agnianisa Salsabila (Mukhtabar Journal of Medical Laboratory Technology, 2023)
Background & Objective: Drinking water is a very important human need. Drinking water that is suitable for consumption must meet established standards, among others, according to the Minister of Health of the Republic of Indonesia No.492/Menkes/IV/2010. This study aims to determine the presence or absence of coliform bacteria in the drinking water of students using the MPN method. Methods: This type of research is descriptive. The sampling was carried out at the Al-Mu'aawanah Islamic boarding school. The results showed that the samples of drinking water for male and female students for microbiological parameters showed that the samples were positive for coliform bacteria. The sample for female students was 22/100 mL, and the sample for male students was 2/100 mL. Based on Permenkes No.472/Menkes/IV/2010, the maximum total concentration of coliform bacteria is 0/100 mL, which means that it is not in accordance with the standards of Permenkes No.472/Menkes/IV/2010, and the growth of faecal coliform bacteria was found in EMB media in both samples. namely the metallic green Escherichia coli bacteria, which indicates that the sample does not meet the microbiological requirements of drinking water.